ECONOMIC DIVERSIFICATION STRATEGIES TO IMPROVE THE WELFARE OF RURAL COMMUNITIES: LITERATURE ANALYSIS AND PRACTICAL IMPLICATIONS - Sigit Sugiardi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
This research discusses economic diversification strategies to improve the welfare of rural communities. The main objective is to analyse the literature on rural economic diversification and identify its practical implications. The method used is a literature study of various scientific sources related to this topic. The results showed that economic diversification can be done through the development of agriculture, tourism, small industry, and creative economy sectors. Supporting factors for successful diversification include government support, community participation, and utilisation of local potential. Challenges faced include limited capital, lack of skills, and limited market access. The practical implication of this research is the need for careful planning in implementing economic diversification strategies in villages, involving various stakeholders, and considering local conditions and potential. In conclusion, economic diversification is a potential strategy to improve the welfare of village communities, but it requires a comprehensive and sustainable approach.